ICAM-1 and ICAM-2 Are Differentially Expressed and Up-Regulated on Inflamed Pulmonary Epithelium, but Neither ICAM-2 nor LFA-1: ICAM-1 Are Required for Neutrophil Migration Into the Airways In Vivo - Chong, Deborah L. W.; Rebeyrol, Carine; José, Ricardo J.; Williams, Andrew E.; Brown, Jeremy S.; Scotton, Chris J.; Porter, Joanna C. (Frontiers in Immunology, 2021)
Neutrophil migration into the airways is an important process to fight infection and is mediated by cell adhesion molecules. The intercellular adhesion molecules, ICAM-1 (CD54) and ICAM-2 (CD102) are known ligands for the neutrophil integrins, lymphocyte function associated antigen (LFA)-1 (αLβ2;CD11a/CD18), and macrophage-1 antigen (Mac-1;αMβ2;CD11b/CD18) and are implicated in leukocyte migration into the lung. However, it is ill-defined how neutrophils exit the lung and the role for ICAMs in trans-epithelial migration (TEpM) across the bronchial or alveolar epithelium. We found that human and murine alveolar epithelium expressed ICAM-1, whilst the bronchial epithelium expressed ICAM-2, and both were up-regulated during inflammatory stimulation in vitro and in inflammatory lung diseases such as cystic fibrosis. Although β2 integrins interacting with ICAM-1 and -2 mediated neutrophil migration across human bronchial epithelium in vitro, neither ICAM-2 nor LFA-1 binding of ICAM-1 mediated murine neutrophil migration into the lung or broncho-alveolar space during LPS-induced inflammation in vivo. Furthermore, TEpM of neutrophils themselves resulted in increased epithelial junctional permeability and reduced barrier function in vitro. This suggests that although β2 integrins interacting with ICAMs may regulate low levels of neutrophil traffic in healthy lung or early in inflammation when the epithelial barrier is intact; these interactions may be redundant later in inflammation when epithelial junctions are disrupted and no longer limit TEpM.